Human Capital Development Strategies in Improving the Performance of The General and Financial Bureaus of The Indonesian Quarantine Agency - Akhmad Alfaraby; Lijan Poltak Sinambela (International Journal of Management Science and Information Technology, 2025)
Human capital is a key resource that plays an important role in organisational performance. Research shows a positive relationship between human capital and organisational performance, such as higher productivity and improved financial performance. Human capital also contributes to competitive advantage, by emphasising the importance of internal resources in organisational strategy. Integrating human capital with organisational strategy through appropriate governance policies and practices can improve individual and organisational performance, and build sustainable competitive advantage. Organisational performance is measured through three dimensions: market, operational and financial performance. Human capital management, rooted in a resource-based view, emphasises the importance of building and managing human capital as a valuable asset. Effective human capital management practices can create knowledge, skills and culture that are difficult to replicate, thus supporting the achievement of organisational goals. In the context of digitalisation, new challenges arise in managing human capital, including the need to change ways of working and upskill employees. Therefore, human capital strategies should focus on employee development, performance management, employee relations, and well-being. As such, human capital management acts as a strategic partner in achieving organisational sustainability and competitiveness in the digital age. Effective integration between human capital strategy and business objectives is key to facing challenges and capitalising on opportunities.